2017
DOI: 10.1155/2017/1908310
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin-Induced Calpain Activation Promotes Protease-Activated Receptor 1 Internalization

Abstract: The serine protease thrombin activates Protease-Activated Receptors (PARs), a family of G-protein-coupled receptors (GPCRs) activated by the proteolytic cleavage of their extracellular N-terminal domain. Four members of this family have been identified: PAR1-4. The activation of Protease-Activated Receptor 1(PAR1), the prototype of this receptor family, leads to an increase in intracellular Ca +2 concentration ([Ca +2 ]i) mediated by G q11 coupling and phospholipase C (PLC) activation. We have previously shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…At very high concentrations, calpain-2 was also shown to cleave PAR2, and the authors suggested that this cleavage event inactivated PAR2 [26]. Recently, calpain-1 was shown to be induced by thrombin-activated PAR1, and subsequently regulated the internalization of PAR1 [85].…”
Section: Cleavage and Activation Of Pars And Signal Transductionmentioning
confidence: 99%
“…At very high concentrations, calpain-2 was also shown to cleave PAR2, and the authors suggested that this cleavage event inactivated PAR2 [26]. Recently, calpain-1 was shown to be induced by thrombin-activated PAR1, and subsequently regulated the internalization of PAR1 [85].…”
Section: Cleavage and Activation Of Pars And Signal Transductionmentioning
confidence: 99%
“…On the other hand, biased PAR1 activation by aPC via a cleavage downstream of the canonical site (R 41 S 42 FLLR 46 //N 47 ) induce opposite effects than thrombin, such as anti-inflammatory effect and endothelial barrier protection [129,130]. PAR1 can also be activated in a biased manner by other proteinases such as MMP-13 [131], plasmin [89], KLKs [106,132], neutrophil elastase [133], proteinase-3 [133], cathepsin-G [134,135], granzyme-A [92,93], and calpain-1 [97,136] through proteolytic cleavage at multiple noncanonical sites (Fig. 5).…”
Section: Proteolytic Cleavage As a Regulator Of Biased Signaling In Parsmentioning
confidence: 99%
“…GPER also contributes to the activation of the phospholipase C (PLC) pathway in other cell types (44). The activation of PLC may lead to an increase in intracellular Ca 2+ and regulated clathrin-dependent endocytosis (45,46). In HepG2 cells, PLCgamma (PLCγ) was activated, and intracellular Ca 2+ release was detected after βE2 treatment.…”
Section: Discussionmentioning
confidence: 99%